Monetary policy, development of financial market and banking lending: An analysis of the bank-lending channel in Malaysia - Ghazali, Noor A.; A. Rahman, Aisyah (Universiti Utara Malaysia, 2001)
Recent of interest in understanding the transmission mechanism of monetary policy focuses on two main channels of explaination, i.e. the money and credit channel. This paper investigates a version of the credit channel, i.e. the bank-lending channel for the Malaysian economy. The bank-lending channel assigns a critical role for the supply of bank loans in transmitting the effect of monetary policy on real economic activities. The study analyzes the effect of monetary policy on ability and willingness of Malaysian banks to issue loan with respect to the development in the open financial market. Specifically it argues on the changes of the pattern of influences as progress in the open financial market takes place.